VAT Media Campaign in Lao PDR Results in a Big Bang for the Buck - Rahman, Shaela; Yang, Ka Ying (World Bank, Washington, DC, 2012)
Working closely with the client, the tax department of Lao PDR, and World Bank colleagues, the Investment Climate Advisory Services team designed and rolled out a multifaceted campaign to introduce a new tax in Lao PDR, one that surpassed our own expectations and contributed to increased registrations and collections. This was the first time such a campaign had been mounted for an investment climate advisory client in Lao PDR, and it happened within a very tight timeframe, so it wasn't all smooth sailing. This smart lesson relates our experiences and lessons along the way, demonstrating in particular how communications, if done well at the project pre-implementation stage, can help build client and partner goodwill for the technical work to follow.